Evaluating Battery‐like Reactions to Harvest Energy from Salinity Differences using Ammonium Bicarbonate Salt Solutions. Issue 9 (31st March 2016) - Kim, Taeyoung; Rahimi, Mohammad; Logan, Bruce E.; Gorski, Christopher A.
Abstract: Mixing entropy batteries (MEBs) are a new approach to generate electricity from salinity differences between two aqueous solutions. To date, MEBs have only been prepared from solutions containing chloride salts, owing to their relevance in natural salinity gradients created from seawater and freshwater. We hypothesized that MEBs could capture energy using ammonium bicarbonate (AmB), a thermolytic salt that can be used to convert waste heat into salinity gradients. We examined six battery electrode materials. Several of the electrodes were unstable in AmB solutions or failed to produce expected voltages. Of the electrode materials tested, a cell containing a manganese oxide electrode and a metallic lead electrode produced the highest power density (6.3 mW m −2 ). However, this power density is still low relative to previously reported NaCl‐based MEBs and heat recovery systems. This proof‐of‐concept study demonstrated that MEBs could indeed be used to generate electricity from AmB salinity gradients. Abstract : Don't waste the heat ! A thermolytic solution of ammonium bicarbonate (AmB) can be used to convert waste heat to electrical energy. By exploiting battery‐like reactions with thermally created high and low concentration AmB solutions, a concentration‐dependent cell voltage was developed, producing a net power density of 6.3 mW m −2 .